The Importance of Balanced Nutrition in Early Childhood and Its Development Programs - Fatimah Zahra Isnaini (Qualitative Research in Early Childhood Education, 2026)
Early Childhood is a critical “golden period” or window of opportunity, during which balanced nutrition serves as a fundamental foundation for optimizing physical growth, cognitive development, and strengthening the immune system. Chronic malnutrition, such as Stunting, during this stage can lead to permanent damage to brain structure and function, significantly reducing children's intellectual potential and learning abilities. Although the importance of nutrition has been widely recognized, the implementation of balanced nutrition in Indonesia still faces multidimensional challenges, particularly due to low nutritional literacy among parents and the lack of structured and integrated nutrition programs in early childhood education institutions. This study aims to analyze the urgency of balanced nutrition and formulate an applicable development program framework to address these challenges. To overcome these barriers, a shift is needed from curative interventions toward a more promotive and preventive approach through an Integrated Balanced Nutrition Development Program. This program is recommended to be designed based on three main pillars: (1) Interactive Nutrition Education for children and parents, including training on My Plate and responsive feeding; (2) Specific Nutrition Interventions through the utilization of local food resources; and (3) Holistic Collaboration among early childhood education institutions as centers for habit formation, families as facilitators, and healthcare professionals for monitoring and intervention. In conclusion, achieving balanced nutrition requires multisectoral collaboration and community empowerment-based programs to create a sustainable optimal nutritional environment for young children.